3-D printer settings effects on the thermal conductivity of acrylonitrile butadiene styrene (ABS). (September 2018) - Sonsalla, Tyler; Moore, Arden L.; Meng, W.J.; Radadia, Adarsh D.; Weiss, Leland
Abstract: Fused deposition modeling (also known as 3-D printing) utilizes a molten plastic filament passed through a heated nozzle to fabricate a three-dimensional object. Various printer settings (i.e. layer height, fill density, print speed, nozzle diameter) of a 3-D printer can be adjusted, which on a macro scale affect the print time and test piece finish (i.e. smaller layer height lead to a fully smooth surface). Many studies have reported effects of printer settings on mechanical properties. This study uses a macroscale and micron-scale approach to characterize effects of 3-D printer settings on thermal conductivity of 3-D printed acrylonitrile butadiene styrene (ABS). The highest thermal conductivity value of 0.25 (±0.05) W/m-K was achieved with a printed layer height of 0.4 mm and 100% fill density. This study shows print times can be reduced by as much as 80% while maintaining thermal performance. These general results influence many commonly available printer materials as well as unique materials under development. Highlights: In parts printed with fused deposition modeling: Increasing layer height increases thermal conductivity In general, increasing fill density increases thermal conductivity Increasing print speed reduces thermal conductivity Nozzle diameter does not significantly affect thermal conductivity Print time can be reduced, while maintaining thermal conductivity performance